DAMPAK STRATEGI PEMBELAJARAN LEWAT VISUALISASI DALAM PENDIDIKAN AGAMA KRISTEN DI ERA MASYARAKAT 5.0 - Tanasyah, Yusak; Putrawan, Bobby Kurnia; Sutrisno, Sutrisno; Iswahyudi, Iswahyudi (SEKOLAH TINGGI TEOLOGI STAR'S LUB LUWUK BANGGAI, 2021)
Technological developments in the 21st century have made enormous changes in modern human civilization today. Internet technology has changed every human life using innovative technology in the palm. In the context of education, especially this visualization learning strategy, this is the impact of renewable learning strategies that help the world of education dashed, measurably and easily accessible anytime and anywhere. Research on the impact of learning strategies through visualization in Christian education in the era of Society 5.0 shows that the challenge of using innovative technology is one of the benefits both educators and students face to innovate in teaching. The most crucial question in education today is the impact of implementing effective visual learning strategies for students in the era of Society 5.0. The result is that the effectiveness of Christian religious education learning strategies through visualization can be measured by the method's ability to enable the target students to achieve the desired learning outcomes of instruction.